Corporate Governance, Likuiditas, Tax Avoidance: Ukuran Perusahaan Sebagai Variabel Moderasi - Isnaini Nur Hanifah (Jurnal Literasi Akuntansi, 2022)
Purpose: This study aims to examine the effect of corporate governance and liquidity on tax avoidance with firm size as a moderating variable. The elements of corporate governance used are independent commissioners and audit committees. Method: The samples was selected using a purposive samplings technique with the result of 22 property and real estate companies listed on the Indonesia Stock Exchange from 2016-2019. The analysis method used in the research is multiple linear analysis and Moderated Regression Analysis. Finding: The results obtained indicate that independent commissioners have no effect on tax avoidance. Audit committee and liquidity have a negative effect on tax avoidance. Firm size is able to moderate the negative effect of the audit committee on tax avoidance, but is not able to moderate the effect of independent commissioners and liquidity on tax avoidance. Novelty: This study considers the effectiveness of the involvement of firm size as a moderating factor of the influence of corporate governance and liquidity on tax avoidance in property and real estate companies.